2015
DOI: 10.1177/1098612x15587955
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for idiopathic cystitis in Norwegian cats: a matched case-control study

Abstract: Several significant differences between cats with FIC and control cats were revealed, and the results support the hypothesis of environmental stress as being a potential factor in the development of FIC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
43
2
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 48 publications
2
43
2
4
Order By: Relevance
“…However, other cats, conflict with other cats, number of litter boxes and diet were not associated with FIC. The third study from Norway identified being overweight, more nervous and having less frequent diet changes as risk factors for FIC, whereas diet type, feeding location, litter box number and care, other cats, conflict with other cats and outdoor access were not associated with altered risk (Lund and others 2016). …”
Section: Epidemiology Of Feline Lower Urinary Tract Diseasementioning
confidence: 99%
“…However, other cats, conflict with other cats, number of litter boxes and diet were not associated with FIC. The third study from Norway identified being overweight, more nervous and having less frequent diet changes as risk factors for FIC, whereas diet type, feeding location, litter box number and care, other cats, conflict with other cats and outdoor access were not associated with altered risk (Lund and others 2016). …”
Section: Epidemiology Of Feline Lower Urinary Tract Diseasementioning
confidence: 99%
“…In contrast, the evidence in feline medicine is not as strong and rather sparse. The health conditions reported to be positively associated with feline O&O include dermatological conditions (Scarlett & Donoghue 1998, Lund et al 2005, Öhlund et al 2018, lameness (Scarlett & Donoghue 1998), musculoskeletal disease (Öhlund et al 2018), hypertrophic cardiomyopathy (Freeman et al 2013, Payne et al 2015, respiratory conditions (Öhlund et al 2018), oral condi tions (Lund et al 2005), lower urinary tract (LUT) conditions (Lekcharoensuk et al 2001, Segev et al 2011, Pusoonthornthum et al 2012, Öhlund et al 2018) -particularly feline idiopathic cystitis (FIC; Cameron et al 2004, Defauw et al 2011, Lund et al 2016, neoplasia (Lund et al 2005) and diabetes mellitus (Scarlett & Donoghue 1998, Lund et al 2005, Haring et al 2012, O'Neill et al 2016, Öhlund et al 2018. The associa tion between diabetes mellitus and O&O is supported by more robust evidence than the other health conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Feline lower urinary tract disease (FLUTD) is one of the most common conditions diagnosed in cats, affecting approximately 1.5–4.6% of the feline population presented in veterinary practices . FLUTD includes several disorders affecting the urinary bladder and/or urethra and is characterised by the presence of non‐specific signs such as stranguria, dysuria, haematuria, pollakiuria and periuria with or without obstruction . Urethral obstruction is a common complication of FLUTD, particularly in male cats, with an incidence of 18–58% …”
mentioning
confidence: 99%
“…Feline idiopathic cystitis (FIC) is deemed the most frequent cause of FLUTD in cats that are less than 10 years old . Other reported identifiable causes of FLUTD include urolithiasis, trauma, anatomical defects, behavioural disorders, neoplasia and urinary tract infection (UTI) . Historically, UTI has been only diagnosed in 1–3% of FLUTD cases .…”
mentioning
confidence: 99%
See 1 more Smart Citation